60+60*1+1=61

Simple and best practice solution for 60+60*1+1=61 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 60+60*1+1=61 equation:


Simplifying
60 + 60 * 1 + 1 = 61

Multiply 60 * 1
60 + 60 + 1 = 61

Combine like terms: 60 + 60 = 120
120 + 1 = 61

Combine like terms: 120 + 1 = 121
121 = 61

Solving
121 = 61

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| (D^4-2D^2+1)y=0 | | 16y-3=10-10y | | 5.4(2x-7)=-18.5 | | -7-2+4q+3q= | | 5e+8=33 | | 9[5-8(x-1)]+6[(5x+2)-8]=17x-336 | | -3d+9d-5+7= | | 40x+4(1.25x)=720 | | 3e+4=13 | | 3t^2-23t+40=0 | | 5.5x+22=0 | | 5v+5=25 | | (X^2-2)*(3-X)= | | 22x-1.1=0 | | K-5=2k-6 | | 6x-15=9x+11 | | 4.5x-13.5=0 | | (X^2-13)*(14-X)= | | (4j-5k)*(5i+5j+7k)=equation | | 3(4-5x/7)=(2x/5)-8 | | 0.5t^2-31t+500=0 | | 3x-12+(3x)+9=0 | | 2.3x+4.6=0 | | 22x^4-5x^3+19x-5x-3=0 | | X^3-2x-2=0 | | 2+3x+-2x^2=0 | | 3x+1=-3x+8 | | -8j/3=9 | | 24=23 | | 2h^5-3h^2+h^3=-1h^6 | | 2.5+10=0 | | -(-2x)=(-20) |

Equations solver categories